Post-Quantum Security for Blockchain and Healthcare Data Management: A Review - Karaduman, Ozgur; Gurbuz, Zeynep Buse; Gencoglu, Muharrem Tuncay; Eren, Haluk (Institute of Electrical and Electronics Engineers Inc., 2025)
The rapid advancement of quantum computing poses a significant threat to classical cryptographic methods used in blockchain-based healthcare systems. Existing security mechanisms such as RSA and ECC are vulnerable to quantum attacks, posing a risk to patient data integrity, confidentiality, and authentication mechanisms. To address this challenge, postquantum cryptographic (PQC) solutions, including lattice-based, hash-based, code-based, and multivariate polynomial-based techniques, have been proposed. This study systematically reviews and classifies PQC methods and their integration into blockchainbased healthcare infrastructures. A three-layer security model is discussed to enhance blockchain resilience against quantum attacks. The study further explores on-chain, off-chain, and crosschain security mechanisms within healthcare applications to ensure secure medical data storage, patient identity management, and interoperability among healthcare providers. The findings suggest that hybrid cryptographic models, combining classical and post-quantum techniques, provide a practical transition strategy for ensuring long-term security in blockchain networks. This research contributes to the field by offering a structured classification of quantum-resistant blockchain security mechanisms and providing insights into future research directions, particularly in the areas of quantum-safe healthcare data management, performance optimization of PQC methods, and the development of quantum-resistant smart contracts. © 2025 IEEE.
9th International Symposium on Innovative Approaches in Smart Technologies, ISAS 2025 -- 27 June 2025 through 28 June 2025 -- Gaziantep -- 211342
Keywords: blockchain; healthcare data; off-chain storage; on-chain security; post-quantum cryptograph; quantum-resistant signature